Hypomethylation at PANDAR promoter progressively induces senescence in adipocyte precursor cells in subjects with obesity and type 2 diabetes - Desiderio, Antonella; Pastorino, Monica; Campitelli, Michele; Prevenzano, Immacolata; De Palma, Fatima Domenica Elisa; Spinelli, Rosa; Parrillo, Luca; Longo, Michele; Milone, Marco; Miele, Claudia; Raciti, Gregory Alexander; Beguinot, Francesco (The FASEB journal, 2024)
The risk of developing type 2 diabetes (T2D) is heterogeneous among individuals with obesity. Functional decline of adipocyte precursor cells (APCs) and accumulation of senescent cells in the subcutaneous adipose tissue contributes to the progression toward T2D. LncRNAs regulate cell senescence and may be implicated in determining this abnormality in APCs. Here, we report that APCs from individuals with obesity show a gradual increase in multiple senescence markers, which worsens in parallel with the progression from normal glucose tolerance (NGT) to impaired glucose tolerance (IGT) or T2D. Transcriptomic analysis identified PANDAR as the top‐ranked lncRNA differentially expressed in APCs from individuals with obesity and T2D and non‐obese subjects. Q‐PCR confirmed PANDAR up‐regulation in APCs from individuals with obesity, at progressively increased levels in those who developed, respectively, IGT and T2D. Bisulfite sequencing and luciferase assays revealed that, in parallel with glucose tolerance deterioration, the −1317 CpG at the PANDAR promoter became hypo‐methylated in obesity, resulting in enhanced PANDAR induction by p53. PANDAR silencing in senescent APCs from individuals with obesity and T2D caused repression of senescence programs and cell cycle re‐entry. PANDAR transcription in white blood cells (WBCs) mirrored that in APCs. Also, individuals with obesity exhibited rescue of PANDAR transcription in WBCs following bariatric surgery, accompanied by enhanced methylation at the regulatory PANDAR −1317 CpG. In conclusion, PANDAR dysregulation is a newly identified mechanism determining the early senescence of APCs from individuals with obesity, which worsens along the progression toward T2D. In the future, PANDAR targeting may represent a valuable strategy to delay this progression. APCs from individuals with obesity show a progressive increase in senescence markers, which worsens with T2D. In APCs from individuals with obesity and T2D, PANDAR is up‐regulated. This results from the hypo‐methylation of the −1317 CpG at the PANDAR promoter. Also, PANDAR silencing in senescent APCs from individuals with obesity and T2D caused repression of senescence programs and cell cycle re‐entry. Here, we reported that PANDAR dysregulation is a new mechanism determining APC early senescence in individuals with obesity and T2D.